Organisational factors affecting turnover intention among female employees in banking industry in Malaysia - Chee, Lyn Swane; Gan, Zhi Dong; Lim, Yeong Yuan; Tiew, Shen Ti; Lee, Woi Jing Jye (2021)
High employee turnover issue can directly influence the company profitability and also lead to several negative results including expensive recruitment cost, production inefficiency and etc. It is undeniably that the costs that need to be used to cover an employee that quit the organisation is enormously high and organisation will be the one to assume all the costs to find another employee to replace the current one. The study aimed to examine the relationship between factors such as organisational cynicism, organisational culture, perceived organisational support, organisational justice towards turnover intention among female employees in the banking industry in Malaysia. The study uses SPSS (Scientific Package for Social Sciences) to run Descriptive Analysis, Reliability Test, and Inferential Analysis including Pearson’s Correlation Coefficient and Multiple Regression Analysis. In addition, PROCESS v3.5 is used to run the mediation analysis. Selangor (included Kuala Lumpur), Penang, and Johor will be targeted as our sampling location. Snowball sampling method is chosen in the study as the data collection method. There are total of 394 responses returned from the respondents from different bank branches and most of the respondents are from junior management and non-managerial position. The analysis discovered that all of the organisational factors have significant relationship with the turnover intention of female employees in banking industry. Besides, the result showed that there is a significant organisational justice and perceived organisational support indirect effect on turnover intention through the organisational commitment among female employees in banking industry in Malaysia.